A new approach to evaluate abandoned mine methane resources based on the zoning of the mining-disturbed strata. (1st July 2023) - Cheng, Ming; Fu, Xuehai; Chen, Zhaoying; Liu, Ting; Zhang, Miao; Kang, Junqiang
Abstract: Abundant abandoned mine methane (AMM) accumulates in the mining-disturbed coal/rock strata in abandoned coal mines. However, the simplified pore and fracture model of the mining-disturbed strata is often adopted to investigate AMM resources. In this case, AMM distribution needs to be more accurate, making it difficult to determine the appropriate location of surface wells. So the question is, how can the pore and fracture be characterized in different zones of the mining-disturbed strata? What is the distribution of AMM resources in the mining-disturbed strata? To address these problems, in this work, the mining-disturbed coal/rock strata of the abandoned mine are divided into five zones. The pore and fracture of the mining-disturbed strata in different zones are characterized by simulation experiments. On this basis, the new evaluation approach of AMM in the mining-disturbed strata is established to reveal the distribution of AMM in each zone. The results show that the mining-disturbed coal/rock strata are divided into five zones: stress concentration zone (I), shear fracture zone (II), separation fracture zone (III), compaction zone (IV), and bottom fracture zone (V). The pore and fracture of coal/rock strata and the distribution of AMM are different in each zone. The AMM resources in the mining-disturbed strata have great potential for development. The AMM in zone I account for 69% of the total, mainly the adsorbed gas in the remaining coal seam affected by mining disturbance. The AMM in the stress relief zone is mostly free gas remaining in the pore and fracture. The fractures in zone II are connected along the horizontal direction, forming a ring fracture body with abundant free AMM resources, which accounted for 19% of the total AMM resources. The AMM in zones III, IV, and V are limited. This work provides a new approach to evaluating the AMM and plays a guiding role in the layout of the surface wells in abandoned mines. Highlights: The mining-disturbed strata can be divided into five zones by stress state. An evaluation approach is proposed to analyze the distribution of AMM resources. Adsorbed AMM is abundant in abandoned mines with low recovery or incomplete mining. The ring fracture body rich in free AMM is formed at the edge of the relief zone.